2003
DOI: 10.1063/1.1557319
|View full text |Cite
|
Sign up to set email alerts
|

Current-free double-layer formation in a high-density helicon discharge

Abstract: A strong, current-free, electric double-layer with eΦ/kTe∼3 and a thickness of less than 50 debye lengths has been experimentally observed in an expanding, high-density helicon sustained rf (13.56-MHz) discharge. The rapid potential decrease is associated with the “neck” of the vacuum vessel, where the glass source tube joins the aluminum diffusion chamber, and is only observed when the argon gas pressure is less than about 0.5 mTorr. The upstream electron temperature Te appears 25% greater than the downstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
275
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(292 citation statements)
references
References 24 publications
15
275
2
Order By: Relevance
“…Understanding the spatial damping of the ion beam is important if this device is to be used as a space thruster as was proposed earlier [2,3]. Further investigations on the 3-D profile of the double layer is needed and optical diagnostics could provide useful informations if the experiment could be reproduced in a device with full optical access to the source tube.…”
Section: A Existence Of a Double Layer And Spatial Dependenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the spatial damping of the ion beam is important if this device is to be used as a space thruster as was proposed earlier [2,3]. Further investigations on the 3-D profile of the double layer is needed and optical diagnostics could provide useful informations if the experiment could be reproduced in a device with full optical access to the source tube.…”
Section: A Existence Of a Double Layer And Spatial Dependenciesmentioning
confidence: 99%
“…In these experiments, a plasma expansion was forced by a strong divergence of a high magnitude magnetic field at very low pressure. Detailed investigations of these currentfree DLs have been performed using electrical measurements [2,[6][7][8][9][10][11], laser induced fluorescence [12][13][14][15][16] and numerical simulations [17,18]. An upstream ionization instability has recently been observed in one of the experimental systems [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the first scheme could be obtained with only one plasma source, the second one requires two independent sources. Note that in this configuration, axial flows could be driven from the magnetic expansion of the plasma (Charles and Boswell 2004;Plihon et al 2007). Alternative schemes such as single grid acceleration of the plasma (Dudin and Rafalskyi 2009) may also be implemented to independently control the ratio of the poloidal (s) and toroidal (t) flows.…”
Section: Machine Description and Capabilitiesmentioning
confidence: 99%
“…Several helicon plasma devices [1][2][3][4], used in studies of warm low-β plasma flow along expanding magnetic fields, have shown the acceleration of plasma to supersonic speeds occurring in short distances, i.e., ∼ 50 Debye lengths, λ D,e , after the field has expanded 10−20%. Theoretical analysis of these results [5][6][7][8] have attributed the ion acceleration to electrostatic layers, single or double, generated by the expanding magnetic field.…”
Section: Introductionmentioning
confidence: 99%